Hadith-Based Ethics of Da’wah: Principles and Contemporary Relevance - Mhd Ary Hamzah; Munandar Munandar; Farid Adnir (Civiliza Publishing, 2026)
Studies on da'wah ethics have generally focused on normative Islamic teachings or contemporary communication practices, yet limited attention has been given to systematically examining the ethical principles of da'wah through a thematic analysis of Hadith and their relevance to the challenges of modern society. This study aims to fill this gap by exploring the ethics of da'wah from the perspective of the Hadiths of Prophet Muhammad SAW and contextualizing their application in contemporary social settings. Employing a library research approach and the thematic (maudhu‘i) method of Hadith analysis, the study identifies key ethical principles, including hikmah (wisdom), mau‘izhah hasanah (good counsel), mujadalah bi al-lati hiya ahsan (courteous dialogue), exemplary conduct (uswah hasanah), non-coercion, and patience. These principles collectively represent a humanistic, persuasive, and socially constructive model of da'wah. The study further demonstrates that a contextual understanding of Hadith is essential for adapting these ethical values to contemporary realities, particularly in responding to pluralism, digital communication, and globalization. The originality of this research lies in its integration of thematic Hadith analysis with contemporary social issues to formulate a Hadith-based framework of adaptive and moderate da'wah ethics. The findings contribute to the development of ethical da'wah models that promote peaceful communication, strengthen social cohesion, and reduce the potential for social conflict in diverse societies.